2012
DOI: 10.4236/ajps.2012.311190
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Antioxidant and Antineoplastic Properties of Italian Saffron (<i>Crocus sativus L</i>.)

Abstract: Saffron, the most expensive spice in the world, is got by Crocus sativus L. stigmas. The production of this substance has attracted human interest, since ancient cultures, for its medicinal and culinary properties. Because of saffron high economic value, sometimes, since Middle Ages, it is adulterated with other vegetal materials, dyes or synthetic molecules. Object of this work was the study of one of the best world saffron: Civitaretenga (AQ, Central Italy) C. sativus. Taste, color and aroma of Civitaretenga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 27 publications
(26 reference statements)
2
58
0
Order By: Relevance
“…Similar results were obtained by Gregory and Menary [18]. Using GC-MS, Cullere et al [10] reported identification of phenylethanol, acetic acid esters while 4-hydroxy-2,5-dimethyl-3(2H)-furanone, geraniol, linalool, acetic acid esters were reported by Carmona et al [19] and flavonoids like kaempferol, quercetin and myricetin have been reported by Gismondi et al [20]. …”
Section: Resultssupporting
confidence: 88%
“…Similar results were obtained by Gregory and Menary [18]. Using GC-MS, Cullere et al [10] reported identification of phenylethanol, acetic acid esters while 4-hydroxy-2,5-dimethyl-3(2H)-furanone, geraniol, linalool, acetic acid esters were reported by Carmona et al [19] and flavonoids like kaempferol, quercetin and myricetin have been reported by Gismondi et al [20]. …”
Section: Resultssupporting
confidence: 88%
“…Human cervical cancer (HeLa) and murine melanoma (B16F10) cells were grown and propagated under standard culture conditions [32,33]. Nanodiamond solutions (previously described) were sonicated before their use, in order to break up possible aggregates.…”
Section: Cell Cultures and Treatmentsmentioning
confidence: 99%
“…The total phenolic and flavonoid content and antioxidant capacities of different plant parts were measured using a DPPH free radical scavenging assay and an ABTS assay, as well as in a C2C12 cell line, to validate the phytomedicinal properties of the significant metabolites identified from the NMR analysis. DPPH and ABTS assays have been previously used to estimate the antioxidant properties of Italian saffron Crocus sativus L. [24], Sideritis italica extracts [25] and the antioxidant properties of Lavandula angustifolia Miller essential oil [26]. Total phenolic and flavonoid content have been previously calculated and related to plant stress in response to tetracycline accumulation [27], in Cordyceps pruinosa mycelia cultivated under different media and light conditions [28] and in Saraca Asoka flowers [29] and African medicinal plants [30].…”
Section: Introductionmentioning
confidence: 99%